The rationale behind Zimbabwe’s foreign policy re-alignment in the context of re-engaging the West (2009 - 2016) - Tigere, Tinashe Kelvin (Midlands State University, 2017)
This research examined the rationale or the fundamental reasons behind the recent Zimbabwe’s foreign policy re-alignment in the context of re-engaging the West. Several aspects were looked at by the researcher so as to establish the reasons why Zimbabwe should engage. The main reason being the current economic situation in Zimbabwe where the Finance Ministry is at times even struggling to pay the civil servants, there is high rate of unemployment and the university graduates are now as good as the rural folk just to mention a few. The researcher used the purposive sampling which is a type of non - probability sampling technique because only crucial and relevant officials were selected from some government ministries and departments, relevant civil society organisations, non-governmental organisations including relevant universities. Data was collected through the use of questionnaires, interviews and observations. Both qualitative and quantitative methods were used. The researcher used tables, charts and graphs to present and analyse data. Finally, the conclusion was that Zimbabwe has a good number of policies that it has to revise so as to promote the re-engagement process. A lot has to be done on the fiscal policy, land reform programme, human rights and all the other actions that are viewed as a threat to international peace and security. This will then allow the West to lift sanctions and Zimbabwe can be eligible for financial aid from the Bretton Woods institutions without any problems. Re-engagement of the West is crucial because it will enable the opening of the lines of credit and investment to promote economic growth. The solution lies in the creation of an enabling environment for bilateral and multilateral co-operation to take place.